KERAGAMAN GENETIK, HERITABILITAS DAN KEMAJUAN GENETIK KARAKTER AGRONOMI PADA POPULASI GALUR F2 HASIL PERSILANGAN - Hakim, Lukman; Suyamto, Suyamto (Jurnal Penelitian Pertanian Tanaman Pangan, 2018)
Genetic variability, heritability estimate and expected genetic advance may be useful to provide the basis for planning of more efficient in selection program. The objectives of this study were to determine genetic variability, heritability and genetic advance of agronomic characters that could be realized through selection of segregation progenies. The F2 soybean progenies derived from two cross combinations and their three parent varieties were evaluated for their genetic variability, heritability and expected genetic advance of agronomic traits at Muneng Experimental Station, Probolinggo, East Java, during dry season of 2016. The experiment was arranged in a randomized block design, with three replications. Seeds of each F2 progenies and their parents were sown in four rows of 4 m length of plots. Plant spacing was 40 cm x 20 cm, with one plant per hill. Plant population of each F2 progenies and their parents were 80 plants in each replication. Among the character observed, number of pods per plant, seed yield per plant and days to maturity had the highest coefficient of variability, with the means of 53.1%, 48.2% and 42,5% respectively. Plant height and seed size had a moderate coefficient of variability, with the means of 33.5% and 35.7%. While the days to flowering, number of branches and number of nodes per plant had the lowest coefficient of variability, and the means were only 19.9%, 14.1% and 15.8% respectively. The heritability estimate of the eight agronomic traits ranged from 18.9%-53.6%. Number of pods per plant and plant height had the highest heritability estimates for the two crosses, and the means were 53.6% and 41.5% respectively. The days to maturity, seed size and days to flowering were also had high heritability estimate of 38.8%, 36.8% and 36.6%. The mean heritability estimates for seed yield per plant, number of nodes and number of branches per plant were the lowest of only 20.6%, 19.7% and 18.9% respectively. Based on the F2 data, selection on the number of pods per plant had the highest expected genetic advance of 44.7%, followed by the days to maturity (41.0%) and the plant height (40.4%). Seed yield per plant, seed size and the days to flowering had a moderate expected genetic advance of 34.8%, 33.4% and 26.8%. The means of expected genetic advance for number of branches and number of nodes per plant were the lowest of 13.8% and 13.9% respectively. In relation to grain yield, the mean heritability estimate for seed yield per plant was low, of only 20.8%. However, considerable high genetic heritability (48.2%) and genetic advance (34.8%) was present on the seed yield per plant.